Weapon use during the index offense: a study among forensic psychiatry patients in Ontario, Canada - Kaggwa, Mark M.; Davids, Arianna; Mohibi, Parwiz; Erb, Bailea; Bradford, John; Chaimowitz, Gary A.; Olagunju, Andrew T. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Understanding the nature and circumstances around the use of weapons to perpetrate an offense among individuals with mental illness is crucial for evidence-informed policies and actions. However, little is known about the prevalence and factors associated with weapon use during index offenses among patients in the forensic system. Therefore, the present study was designed to address this gap and determine the prevalence and the patient and victim characteristics associated with weapon use during the index offense in a Canadian province. Methods This retrospective exploratory study utilized data extracted from the Ontario Review Board reports of 2014/15. Data was analyzed using Stata, and logistic regression was employed to determine the factors associated with weapon use. Results Approximately half (48.11%) of the individuals included in this analysis (n = 819) used weapons during their index offense as an instrument of violence. Both patient-related and victim-related factors had a statistically significant association with weapon use during index offenses. Specifically, two patient-related factors (including a history of hospitalization prior to the index offense and diagnosis of personality disorder) were associated with lower odds of weapon use during the index offense. However, only prior hospitalization remained statistically significant after adjusting for victims’ factors. Victim-related factors were associated with both lower and higher odds of weapon use during the index offense. The highest odds of weapon use were found if the victim was an extended family member of the patient, followed by sibling, lover/partner/spouse, parent, and then adult acquaintance. The odds of weapon use during the index offense were lower if victims were healthcare workers, law enforcement professionals, and females when compared to adult strangers. Conclusion The study highlights the significant role of both patients’ and victims’ characteristics as important factors associated with weapon use during index offenses among forensic patients. Notably, prior hospitalization emerged as a crucial factor with a reduced likelihood of weapon use. Implicitly, this underscores the importance of risk mitigation strategies.